Poxviral Targeting of Interferon Regulatory Factor Activation. - Brady, Gareth (My University, 2020)
As viruses have a capacity to rapidly evolve and continually alter the coding of their protein repertoires, host cells have evolved pathways to sense viruses through the one invariable feature common to all these pathogens—their nucleic acids. These genomic and transcriptional pathogen-associated molecular patterns (PAMPs) trigger the activation of germline-encoded anti-viral pattern recognition receptors (PRRs) that can distinguish viral nucleic acids from host forms by their localization and subtle differences in their chemistry. A wide range of transmembrane and cytosolic PRRs continually probe the intracellular environment for these viral PAMPs, activating pathways leading to the activation of anti-viral gene expression. The activation of Nuclear Factor Kappa B (NFκB) and Interferon (IFN) Regulatory Factor (IRF) family transcription factors are of central importance in driving pro-inflammatory and type-I interferon (TI-IFN) gene expression required to effectively restrict spread and trigger adaptive responses leading to clearance. Poxviruses evolve complex arrays of inhibitors which target these pathways at a variety of levels. This review will focus on how poxviruses target and inhibit PRR pathways leading to the activation of IRF family transcription factors.
PUBLISHED
Keywords: protein repertoires; anti-viral pattern recognition receptors (PRRs); viral PAMPs; protein repertoires; anti-viral pattern recognition receptors (PRRs); viral PAMPs; Immunology, Inflammation & Infection